Soil water regime and nutrient availability modulate fine root distribution and biomass allocation in amazon forests with shallow water tables - Checa-Cordoba, Edher; Esteban, Erick J. L.; Emilio, Thaise [UNESP]; Lira-Martins, Demétrius; Schietti, Juliana; Pinto, José P. V.; Tomasella, Javier; Costa, Flávia R. C. (Springer Nature, 2024)
Background and aims: Shallow water table (WT) forests (representing ~ 50% of Amazonian land areas) exhibit different characteristics and functioning compared to the more widely studied deep WT forests. However, less is understood about the determinants of biomass allocation to aerial and belowground components in shallow WT forests. Here we investigate how limitations imposed by soil physical properties influence the distribution of fine root biomass and the partitioning of biomass (BGB: AGB ratio) in shallow WT forests, and the relationships with their stand structure. Methods: We used extensive ground-based data on soil properties, soil nutrients, WT monitoring, and direct biomass measurements along a 600 km transect of shallow WT forests in the central Amazon region. Results: Soil water excess, due to a wetter climate or a persistently shallow WT, restricts fine-root distribution to the upper soil layers. This restriction, alone or combined with phosphorus limitation, leads to a higher biomass allocation belowground, associated with stand structures characterized by a higher density of smaller trees. Opposite patterns are found where the soil experiences no excess water or does so infrequently. Soil nutrient availability contributes to biomass partitioning, but with WT regimes strongly modulating its effects. Conclusion: Finding that soil water regime have an overarching control on fine-root distribution and biomass partitioning in shallow WT forests challenges the dominant perspective of allocation being mostly affected by soil nutrients and climate. These findings improve our understanding of a large fraction of the Amazon rainforest, with important implications for modeling and predicting its functioning as a carbon store and the regulation of biogeochemical cycles.
Keywords: Amazonia; BGB:AGB ratio; Fine-root biomass; Forest stand structure; Water table